Protective effect of HPS against irinotecan-induced intestinal injury in drosophila and mice via modulation of inflammation, oxidation, and gut microbiota. - Li, S.; Chen, Q.; Du, X.; Gao, R.; Li, L.; Li, B.; Han, S.; Zhang, L.; Xiu, M.; He, J.; Lin, X. (International Journal of Biological Macromolecules, 2025)
Intestinal mucositis is a common and debilitating complication of the chemotherapeutic agent irinotecan (CPT-11), characterized by intestinal barrier disruption, oxidative stress, inflammation, and gut microbiota dysbiosis. Radix Hedysari polysaccharides (HPS) possess anti-inflammatory, antioxidant, and microbiota-regulating properties, but their protective effects against CPT-11-induced intestinal injury remain unclear. In this study, we investigated the protective effect and mechanism of HPS in CPT-11-induced intestinal mucositis using Drosophila melanogaster and BALB/c mouse models. HPS supplementation significantly improved survival and locomotor activity in CPT-11-induced flies, and ameliorated intestinal phenotypes including excessive feeding, increased excretion, crop enlargement, shortened gut length, impaired acid-base balance, and elevated intestinal cell death. HPS also suppressed reactive oxygen species (ROS) levels and modulated antioxidant-related genes (gstD1, cat, sod1, sod2) and the JAK pathway (STAT92E, UPD3, UPD3-1) in fly guts. In mice, administration of HPS reversed the CPT-11-induced gut microbial dysbiosis, restored microbial diversity, and suppressed serum pro-inflammatory cytokines (TNF-? and IL-6). Mechanistic studies revealed that HPS alleviated colonic injury by up-regulating the Keap1/Nrf2 antioxidant response and down-regulating the JAK1/STAT6 inflammatory signaling. These findings suggest that HPS has a protective role in CPT-11-induced intestinal mucositis via antioxidant, anti-inflammatory, and microbiota-modulatory activities, supporting its potential as a therapeutic agent for chemotherapy-induced intestinal injury.